The lady in the van [videorecording (DVD)] - Smith, Maggie, 1934-; Jennings, Alex; Broadbent, Jim (Sony Pictures Home Entertainment, 2016)
The film tells the true story of the relationship between Alan Bennett and the singular Miss Shepherd, a woman of uncertain origins who 'temporarily' parked her van in Bennett's London driveway and proceeded to live there for fifteen years.